Traditional Market Might Against Modern Competitive Fight - Indah Murdianingrum; Supriyono Supriyono; Sutono Sutono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Traditional markets have a strategic role in the local economy, yet they face increasing competitive pressure due to the rise of modern markets that offer convenience, cleanliness, and service efficiency. This research aims to formulate a competitive advantage strategy for Pasar Jepara I, Jepara Regency, in facing competition from modern markets using the Participatory Appraisal of Competitive Advantage (PACA) approach. This study employs a descriptive qualitative method with the PACA approach, involving the active participation of local stakeholders. Data collection was conducted through field observations, in-depth interviews, and documentation with 17 informants consisting of traders, market managers, consumers, suppliers, and the Jepara Regency Office of Industry and Trade. Data analysis used an interactive model including data reduction, data presentation, and conclusion drawing, with data validity tested through triangulation of sources, techniques, and time. The research results indicate that Pasar Jepara I has competitive strengths rooted in social capital, personal relationships between traders and buyers, price flexibility through bargaining, the availability of fresh local products, and its inherent cultural value. However, the market's competitiveness is still constrained by inadequate infrastructure, weak collaborative governance, a lack of innovation and technology utilization, and a suboptimal bargaining position with suppliers. This study recommends an integrated strategy encompassing strengthening differentiation based on cultural experience, collective adoption of digital technology, building strategic partnerships with local suppliers, strengthening trader institutions, and improving service quality and market facilities. The participatory PACA-based approach proved effective in exploring local potential and formulating contextual, adaptive, and sustainable strategies to enhance the competitiveness of traditional markets amidst the dominance of modern markets.